Good Corporate Governance, Pengungkapan Sustainability Report dan Manajemen Laba terhadap Nilai Perusahaan - Maria Dwi Jemunu; Gaguk Apriyanto; Parawiyati Parawiyati (AFRE (Accounting and Financial Review), 2020)
This study aims to examine and provide empirical evidence of the impact of good corporate governance and sustainability report disclosure on firm value with earning management as an intervening variable. The firm value measured by price to book value, good corporate governance measured by meeting frequency of audit committee and percentage of the independent commissioner on board, sustainability report disclosure measured by the number of items disclosed divided by the items regulated in the GRI, earning management measured by discretionary accruals. The sampling technique is purposive sampling. The number of samples used in this study is 42 companies listed on the Indonesia Stock Exchange in 2018-2019. The data are analyzed using path analysis. The results showed that the audit committee has a significant influence on earning management. Sustainability report disclosure and the independent commissioner have no significance to the earning management. Sustainability report disclosure and the independent commissioner have a significant influence on firm value. Audit committee and earning management have no significant influence on firm value. Earnings management does not mediate the relationship between audit committee, independent commissioners, and sustainability report disclosure on firm value.DOI: https://doi.org/10.26905/afr.v3i2.5195